2022
DOI: 10.1113/jp282402
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cardiomyocyte circadian clocks in ion channel regulation and cardiac electrophysiology

Abstract: Daily variations in cardiac electrophysiology and the incidence for different types of arrhythmias reflect ≈24 h changes in the environment, behaviour and internal circadian rhythms. This article focuses on studies that use animal models to separate the impact that circadian rhythms, as well as changes in the environment and behaviour, have on 24 h rhythms in heart rate and ventricular repolarization. Circadian rhythms are initiated at the cellular level by circadian clocks, transcription–translation feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…4,30,[36][37][38] These studies were supported by data showing that ablation of SCN or transgenic mice lacking the core circadian clock transcription factor Bmal1 (e.g., Bmal1 −/− ) did not have a 24-hour rhythm in HR. [39][40][41] L-RF is not thought to impact the circadian clock mechanism in the SCN; 9 therefore, it was surprising that our previous work demonstrated that L-RF caused a large phase shift in the 24-hour rhythm of the HR. 6 L-RF in mice also shifts the phase of circadian gene expression in peripheral tissues, including the heart, to align with the timing of feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,30,[36][37][38] These studies were supported by data showing that ablation of SCN or transgenic mice lacking the core circadian clock transcription factor Bmal1 (e.g., Bmal1 −/− ) did not have a 24-hour rhythm in HR. [39][40][41] L-RF is not thought to impact the circadian clock mechanism in the SCN; 9 therefore, it was surprising that our previous work demonstrated that L-RF caused a large phase shift in the 24-hour rhythm of the HR. 6 L-RF in mice also shifts the phase of circadian gene expression in peripheral tissues, including the heart, to align with the timing of feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several studies implicate the cardiomyocyte circadian clock in regulating gene expression essential for cardiac excitability, cardiac electrophysiology, and HR. 18,35,40,[42][43][44][45] One might predict then that L-RF shifts the phase of cardiomyocyte gene expression to facilitate the phase shift in HR and cardiac electrophysiology. However, genetically disrupting the cardiomyocyte-specific circadian clock (by inducing the deletion of Bmal1) does not abolish the L-RF mediated phase shift in the daily HR and cardiac electrophysiological rhythms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The cardiomyocyte clock seems to prevent abnormal QT-interval prolongation. 112 In hearts from patients with advanced heart failure, some genes known to be involved in electrical properties and arrhythmias showed strong circadian expression patterns. 22 There also seems to be a diurnal variation in the incidence of arrhythmias requiring implantable cardioverter defibrillator therapy in patients with heart failure.…”
Section: Electrophysiologymentioning
confidence: 99%
“…Indeed, this delayed repolarization was readily reversed upon application of pyruvate (i.e., lowering [NADH] i :[NAD + ] i ) indicating the rapid reversibility of redox effects on the cardiac action potential. Beyond regulating cardiac electrophysiology upon acute changes in the cardiac workload, it is plausible that this mechanism to some extent underlies diurnal oscillations in heart rate and ventricular repolarization [ 93 ]. Surprisingly, redox modulation of repolarization requires the presence of both β subunits [ 9 , 87 ], indicating that Kvβ1 and Kvβ2 subunits may function together to confer metabolic sensitivity of current density and action potential duration.…”
Section: Metabolic Regulation Of Cardiac Repolarizationmentioning
confidence: 99%